2021
DOI: 10.1039/d1ma00163a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decarboxylation for the generation of hierarchical porosity in isostructural metal–organic frameworks containing open metal sites

Abstract: The effect of metal-cluster redox identity on the thermal decarboxylation of a series of isostructural metal-organic frameworks (MOFs) with tetracarboxylate-based ligands and trinuclear μ3-oxo clusters was investigated. The PCN-250 series...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This is indicative of the noticeably stronger Fe–C binding strengths. Metal identity and oxidation state have been known to influence other properties of PCN-250 as well. , Additionally, there was a slight increase in the observed acetylene carbon–carbon bond length. The bond length of acetylene (1.1974 Å as a free molecule) was observed to increase from 1.2007 in the Fe­(III) system all the way to 1.2018 in the nickel-bound Fe 2 Ni system.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This is indicative of the noticeably stronger Fe–C binding strengths. Metal identity and oxidation state have been known to influence other properties of PCN-250 as well. , Additionally, there was a slight increase in the observed acetylene carbon–carbon bond length. The bond length of acetylene (1.1974 Å as a free molecule) was observed to increase from 1.2007 in the Fe­(III) system all the way to 1.2018 in the nickel-bound Fe 2 Ni system.…”
Section: Resultsmentioning
confidence: 98%
“…For comparison, two alternative samples were utilized to determine the performance of reducibility, open metal site formation, and backdonation: PCN-250-Al, which has not been observed to undergo a reductive decarboxylation mechanism, 30 and PCN-250-Fe 2 Ni, which is already in a mixed valent Fe(III)/Ni(II) state, 30 were also subjected to a 250 °C activation and acetylene adsorption experiments (Tables S6 and S7 and Figures S23−S25). The nonreducible Al centers result in lower gas uptake performance compared to the standard Fe 3 variant (Figure S23) while also resulting in a heat of adsorption after 250 °C activation that is nearly identical to that of the 150 °C-activated PCN-250-Fe (Figure S26a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powder patterns, N 2 isotherms, and porosity measurements matched well with previous reports (shown in the Supporting Information). 43−46 In the analogues of PCN-250-M, where M = Al, In, or Sc (also called Al-soc-MOF-1d, In-soc-MOF-1a, and Sc-ABTC/socMOF), 43,45,47,48 the structures do not undergo thermal generation of open metal sites. 43 However, we previously reported that PCN-250-Fe could undergo thermal decarboxylation under standard activation conditions, resulting in open metal sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43−46 In the analogues of PCN-250-M, where M = Al, In, or Sc (also called Al-soc-MOF-1d, In-soc-MOF-1a, and Sc-ABTC/socMOF), 43,45,47,48 the structures do not undergo thermal generation of open metal sites. 43 However, we previously reported that PCN-250-Fe could undergo thermal decarboxylation under standard activation conditions, resulting in open metal sites. 49 Therefore, to avoid the influence of open metal site formation and to provide an accurate comparison between the isomorphs, the Fe-based material was also activated under supercritical CO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%